(untitled) (International Journal of Engineering and Computer Science, 2017)
Ayurveda has used mineral and herbo mineral substances in therapeutics since time immemorial. But with the recent questions raised regarding the toxicity of Ayurvedic formulations, there is a need to scientifically evaluate and establish the safety of such preparations. Kajjali is a predominantly mineral preparation containing Mercury and Sulphur. It forms the base for numerous preparations and extensively used. As per authoritative texts of Ayurveda, mercury extracted from Cinnabar is to be used in all formulations. This extraction may not be economically viable and simple process prompting the use of samples of Mercury available in the market. The present study aims to evaluate the toxicity study of three samples of Kajjali prepared using three different samples of Mercury (one extracted from cinnabar and two other samples available in the market). No toxicity signs were observed in Wistar rats either in acute or sub acute toxicity study for any of the samples. No mortality was observed. Histopathology study indicated maximum organ damage in the group administered Kajjali prepared from market sample Parada and the least in group administered branded sample Parada prepared Kajjali. Hingulottha Parada prepared Kajjali showed moderate organ damage.